Hubungan Person Job-Fit dengan Keterlibatan Kerja pada Karyawan Generasi Milenials di Perusahaan X - Wiweko, Winny Angelica; Kurniawan, Jimmy Ellya (Psychopreneur Journal, 2020)
Work Engagement is one of the interesting topics to be discussed, especially in the world of work. Some previous studies show less specific results related to work engagement, especially the work engagement of millennial generation. Job satisfaction and work motivation are one of the factors that influence job engagement. These factors are actually discussed in Person Job Fit, which discusses the suitability of the character of the job with individual competencies. The purpose of this study is to provide insight into the important person job fit in increasing work engagement in millennial generation employees. This study uses correlational quantitative research methods to see the relationship between the two variables and uses questionnaires as a data collection tool. This study succeeded in gathering data of 157 respondents from company X which is engaged in housing. The results of this study indicate a significant relationship between work engagement with Person Job Fit (ρ: 0.534). If viewed from the dimension of person job-fit, the dimensions of vigor and dedication have a positive relationship with work engagement, while the absorption dimension does not have a relationship with work engagement.